Assessing online and face-to-face collaboration in a hybrid interdisciplinary course: Analysis of the pertinence of a questionnaire - Raynault, Audrey; Béland, Sébastien; Durand, François; Fernandez, Nicolas; Heilporn, Géraldine (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2022)
Universities are offering hybrid interprofessional health sciences collaboration education courses to address the challenges of schedule synchronization, silos, and communication. This article focuses on analyzing the psychometric quality of a questionnaire used in a setting where interprofessional teams collaborated online and face-to-face in a hybrid university health sciences course. This questionnaire was originally designed for people in the working world in order to assess the constructs of collaboration (communication, synchronization and explicit and implicit coordination) mobilized in the face-to-face setting. The results of the second order confirmatory factor analyses support its use in an academic context and support the metric qualities of the original questionnaire. Online and face-to-face collaboration could be measured using this questionnaire in a hybrid university pedagogical context. The study mobilizes knowledge about the evaluation of collaboration, an avenue that little research has taken to date.